Phlebotomy resulting in controlled hypovolaemia to prevent blood loss in major hepatic resections (PRICE-1): a pilot randomized clinical trial for feasibility. Issue 7 (22nd January 2020) - Martel, G; Baker, L; Wherrett, C; Fergusson, D A; Saidenberg, E; Workneh, A; Saeed, S; Gadbois, K; Jee, R; McVicar, J; Rao, P; Thompson, C; et al.
Abstract: Background: Major liver resection is associated with blood loss and transfusion. Observational data suggest that hypovolaemic phlebotomy can reduce these risks. This feasibility RCT compared hypovolaemic phlebotomy with the standard of care, to inform a future multicentre trial. Methods: Patients undergoing major liver resections were enrolled between June 2016 and January 2018. Randomization was done during surgery and the surgeons were blinded to the group allocation. For hypovolaemic phlebotomy, 7–10 ml per kg whole blood was removed, without intravenous fluid replacement. Co-primary outcomes were feasibility and estimated blood loss (EBL). Results: A total of 62 patients were randomized to hypovolaemic phlebotomy (31) or standard care (31), at a rate of 3·1 patients per month, thus meeting the co-primary feasibility endpoint. The median EBL difference was −111 ml ( P = 0·456). Among patients at high risk of transfusion, the median EBL difference was −448 ml ( P = 0·069). Secondary feasibility endpoints were met: enrolment, blinding and target phlebotomy (mean(s.d.) 7·6(1·9) ml per kg). Blinded surgeons perceived that parenchymal resection was easier with hypovolaemic phlebotomy than standard care (16 of 31 versus 10 of 31 respectively), and guessed that hypovolaemic phlebotomy was being used with an accuracy of 65 per cent (20 of 31). There was no significant difference in overall complications (10 of 31 versus 15 of 31 patients), major complications or transfusion. Among those at high risk, transfusion was required in two of 15 versus three of nine patients ( P = 0·326). Conclusion: Endpoints were met successfully, but no difference in EBL was found in this feasibility study. A multicentre trial (PRICE-2) powered to identify a difference in perioperative blood transfusion is justified. Registration number: NCT02548910 ( http://www.clinicaltrials.gov ). Graphical Abstract: A feasibility RCT comparing hypovolaemic phlebotomy with standard care was undertaken in patients having major liver resection. This trial successfully met its feasibility endpoints, but did not identify a significant difference in blood loss. Hypovolaemic phlebotomy appeared safe and its use in patients at a high risk of transfusion deserves further study. Supports a multicentre trial